Left Ventricular Global Function Index and Myocardial Contraction Fraction on 2D Echocardiography as Integral Parameters in Patients with Coronary Artery Disease - Oksana Yu. Marchenko; Nadiya M. Rudenko; Vladyslav Kavalerchyk (Ukrainian Journal of Cardiovascular Surgery, 2022)
Patients with coronary artery disease (CAD) form a large group among all patients with cardiovascular diseases. Atherosclerosis, as one of the main pathogenetic mechanisms in adverse cardiovascular events development, is one of the leading causes of disability and mortality. Echocardiography is one of the main imaging techniques in managing cardiovascular patients. In search of a new parameter that would reflect both the morphological and functional LV changes, more and more attention has recently been paid to integrated indicators such as the left ventricular global function index (LVGFI) and myocardial contraction fraction (MCF). These parameters are independent predictors of heart failure and cardiovascular diseases.The aim. To evaluate the prognostic value of left ventricular global index and myocardial contraction fraction based on 2D echocardiography results in patients with CAD.Materials and methods. Patients with CAD confirmed by coronary angiography were included in the prospective clinical study. Thirty patients without CAD were a control group, 35 patients had single vessel lesion, 66 had multivessel CAD. LVGFI and MCF were calculated using 2D echocardiography technique.Results. The groups were comparable with respect to age, body mass index (BMI) and comorbidities. The mean age of the patients in group I was 60.53±1.77 years. In group II, the mean age was the highest, 64.31±1.62 years, and in group III the participants were 63.0±1.14 years old. The data indicate the absence of a significant difference (p = 0.39) in the age structure of the patients. In the control group, women predominated (70%), compared to groups II and III, where the proportion of women was 31.2% and 21.2%, respectively (p = 0.0001). The highest BMI classified as obesity class 1 was observed in the first group: 31.74 ± 1.09 kg/m2. Group III had BMI of 30.71 ± 0.62 kg/m2, which also indicates obesity class 1. Group II had the lowest BMI: 29.76 ± 0.77 kg/m2, but the difference between the groups was insignificant (p = 0.432). LVGFI and MCF differed significantly among groups (р=0.003 and р=0.004, respectively). MCF was the highest in patients with multivessel disease – 35.0% (27.71; 42.0), and the lowest in the group with no vascular lesions – 42.29% (36.35; 52.21). LVGFI also was different among the groups. It was the lowest in group III (24.91% [19.22; 30.48]), and the highest in group I (30.85% [25.46; 37.13]).Conclusions. MCF and LVGFI are closely related to the degree of coronary artery involvement. These integral parameters may be used as non-invasive markers of more significant coronary arteries involvement.